Dynamic regulation of extracellular ATP in Escherichia coli - Alvarez, Cora Lilia (2017)
We studied the kinetics of extracellular ATP (ATPe) in Escherichia coli and their outer membrane vesicles (OMVs) stimulated with amphipatic peptides melittin (MEL) and mas-toparan 7 (MST7). Real-time luminometry was used to measure ATPe kinetics, ATP release, and ATPase activity. The latter was also determined by following [32P]Pi released from [γ-32P]ATP. E. coli was studied alone, co-incubated with Caco-2 cells, or in rat jejunum segments. In E. coli, the addition of [γ-32P]ATP led to the uptake and subsequent hydrolysis of ATPe. Exposure to peptides caused an acute 3-fold (MST7) and 7-fold (MEL) increase in [ATPe]. In OMVs, ATPase activity increased linearly with [ATPe] (0.1-1 mM). Exposure to MST7 and MEL enhanced ATP release by 3-7 fold, with similar kinetics to that of bacteria. In Caco-2 cells, the addition of ATP to the apical domain led to a steep [ATPe] increase to a maximum, with subsequent ATPase activity. The addition of bacterial suspensions led to a 6-7 fold increase in [ATPe], followed by an acute decrease. In perfused jejunum segments, exposure to E. coli increased luminal ATP 2 fold. ATPe regulation of E. coli depends on the balance between ATPase activity and ATP release. This balance can be altered by OMVs, which display their own capacity to regulate ATPe. E. coli can activate ATP release from Caco-2 cells and intestinal segments, a response which in vivo might lead to intestinal release of ATP from the gut lumen.